Radiologic pleuroparenchymal fibroelastosis-like lesion in connective tissue disease-related interstitial lung disease. - Yasunori Enomoto; Yutaro Nakamura; Thomas V Colby; Takeshi Johkoh; Hiromitsu Sumikawa; Koji Nishimoto; Katsuhiro Yoshimura; Sayomi Matsushima; Yoshiyuki Oyama; Hironao Hozumi; Masato Kono; Tomoyuki Fujisawa; et al. (PLoS ONE, 2017)
Radiologic pleuroparenchymal fibroelastosis (PPFE)-like lesion including pulmonary apical cap can be occasionally observed in clinical settings. However, the significance of radiologic PPFE-like lesion is unclear in connective tissue disease (CTD)-related interstitial lung disease (ILD).A total of 113 patients with CTD-related ILD were enrolled and assessed for radiologic PPFE-like lesion, which was defined as bilateral, upper lobe, and subpleural dense consolidations with or without pleural thickening on chest high-resolution computed tomography. The clinical, radiologic, and pathologic characteristics were evaluated.Radiologic PPFE-like lesion was found in 21 patients (19%) and were relatively frequent in those with systemic sclerosis (6/14: 43%) and primary Sjögren's syndrome (4/14: 29%). Patients with PPFE-like lesion were significantly older, had lower body mass index, higher ratio of residual volume to total lung capacity, and higher complication rate of pneumothorax and/or pneumomediastinum than those without. Twelve of the 21 patients were diagnosed radiologically as usual interstitial pneumonia (UIP) or possible UIP pattern. Two of three patients who underwent surgical lung biopsy of the upper lobes showed UIP on histopathology. Another patient was confirmed to have upper lobe PPFE on autopsy. During the clinical course, progression of the radiologic PPFE-like lesions was observed in 13 of 21 patients. Six patients died (mortality rate: 29%) and their PPFE-like lesions were commonly progressive. In the total cohort, our multivariate analysis identified the presence of PPFE-like lesion as a significant risk factor for respiratory death (hazard ratio: 4.10, 95% confidence interval: 1.33-12.65, p = 0.01).In patients with CTD-related ILD, radiologic PPFE-like lesion, which may present as not only PPFE but also apical cap and upper lobe subpleural fibrosis commonly due to UIP, was not uncommon and was associated with poor prognosis. Clinicians should be cautious with this radiologic finding, particularly when it is progressive.